2010
DOI: 10.1007/s11064-009-0118-2
|View full text |Cite
|
Sign up to set email alerts
|

Cynomorium songaricum Extracts Functionally Modulate Transporters of γ-Aminobutyric Acid and Monoamine

Abstract: Cynomorium songaricum Rupr. (SY) is a central nervous system-oriented herb material that has actions of anti-dementia, anti-epilepsy, and anti-stress. It is unclear whether SY would be biologically active in functionally regulating neurotransmitter transporters. Here, we assessed these potential actions using Chinese hamster ovary cells expressing gamma-aminobutyric acid (GABA) transporter (GAT-1), dopamine transporter (DAT), norepinephrine transporter (NET), or serotonin transporter (SERT) (i.e. G1, D8, N1, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…CS might play a role in regulation of neurotransmitter transport. Based on screening of cells expressing various neurotransmitter transporters, CS extracts raised dopamine and norepinephrine uptakes but showed decreases in GABA and serotonin [43]. The regulation of synaptic transmission activity by transmitter systems is frequently correlated with cognitive performance.…”
Section: Discussionmentioning
confidence: 99%
“…CS might play a role in regulation of neurotransmitter transport. Based on screening of cells expressing various neurotransmitter transporters, CS extracts raised dopamine and norepinephrine uptakes but showed decreases in GABA and serotonin [43]. The regulation of synaptic transmission activity by transmitter systems is frequently correlated with cognitive performance.…”
Section: Discussionmentioning
confidence: 99%
“…Interest in these plants has increased in recent years, and they are being extensively collected from wild populations for use in herbal medicines, causing a dramatic decline of this herbal resource. The chemical components and therapy functions of C. songaricum have been studied in the past three decades [10][11][12][13][14][15][16][17]. However, the nutritional relationship of C. songaricum with its hosts has been little studied.…”
Section: B Amentioning
confidence: 99%
“…(CS) is a well-known root-parasitic plant and is distributed throughout northwest China [13]. Cynomorium songaricum extract (CSE) has been widely used as Chinese herbal remedy for problems such as sexual dysfunction, renal disease, and lumbar weakness [14].…”
Section: Introductionmentioning
confidence: 99%
“…Among the chemical compounds in CS, flavonoids have antioxidant effects, and certain types of flavonoids are involved in neuroprotection and hippocampal neurogenesis [17-19]. It has also been reported that CSE modulates γ-aminobutyric acid (GABA) and monoamine transporters, both of which are involved in hippocampal neurogenesis [13]. …”
Section: Introductionmentioning
confidence: 99%